O poder nas organizações : um estudo preliminar a partir da percepção dos trabalhadores - Silva, Carliene Freitas da (2007)
Power is a complex and dynamic phenomena which has been investigated by different sciences. In work organizations its relevance is observed by the increasing number of publications. However, qualitative studies that contemplate Brazilian workers`s perceptions, investigating the possible dimensions of this phenomena, are rare. Therefore, the aim of this study was to investigate the workers`s perception, trying to grasp the meaning and the dimensions of organizational power, focusing mainly the dimension of power games . This research was characterized as an exploratory study in which have taken part ten workers of both genders, coming from public and private organizations in different areas of activities, occupying different posts and who have been working for the organization for at least six months. To data collection it was used a guided and deep interview. To data analysis it was used the content analysis technique. The data analysis resulted in eleven (11) categories which were discussed, separately , according to the researched literature: a) power conceptions; b) who has the power in the organizations; c) types and sources of power; d) informal strategies used by bosses and subordinated workers to reach power positions, to use it and to maintain it, and to react to other powerful persons; e) exercise of legitimate power practised by the bosses; f) strategies of exercise and maintenance of power practised by the bosses; g) reactions of subordinated workers to the legitimate power, and strategies to deal with superiors; h) consequences of the established power relation; i)reasons which make people take part in power games to reach higher positions and keep them; j) organization characteristics that affect the power relations; k) personal characteristics that influence the power relations. The results have contributed to understand the various faces of power in organizations and from them it was possible to propose a definition of power games as a kind of relation, between two actors (boss/subordinated, boss/boss, subordinated/subordinated), who use different means, in an alternated action/reaction movement, to reach and/or keep power positions. This relation can be influenced by organizational and personal characteristics, besides having a positive or negative result. Future researches can use the dimensions identified in this study enhancing the understanding of power in work organizations.